Efektifitas Jamur Metharhizium anisopliae Menghambat Perkembangan Hama Uret pada Tanaman Cincau Hitam (Mesona palustris BL) - Wuye Ria Andayanie (JURNAL AGRI-TEK : Jurnal Penelitian Ilmu-Ilmu Eksakta, 2019)
Black grass jelly plants can be used as conservation plants. However, uret pests (Leucopholis rorida F.) are often complained that eat the base of the stems, flowers and roots at night. This study aims to determine: 1) the effect of M. anisopliae fungi on uret pests, (2) the level of susceptibility of uret pests, and (3) M. anisopliae fungal effectiveness on uret pests. This study used a completely randomized design (CRD) with 4 treatments and 5 replications. Data from the observations were analyzed using analysis of variance (ANOVA) with Duncan's Multiple Range Test (DMRT) 5% test carried out when diversity analysis showed a real effect. Uret mortality monitoring will be carried out after the application of fungi. by observing each uret and calculating the amount of uret mortality and average plant growth. The highest percentage of second instar larvae from uret was found in treatment P4 (manure and fungi were incubated for 72 hours at the next temperature of 28 oC applied to the field with straw mulch) which was 82, 98% at 12 days after application of fungi. The average growth of plants consisting of: root length, root volume, stem diameter and number of shoots was also found in treatment P4 (manure and fungi were incubated for 72 hours at the next 28 oC, applied to the field with straw mulch), respectively amounting to 12.45; 5.70; 1.88; 12,15. Dead larvae emit fluids such as ethanol and their bodies are weak, then the body dries and hardens and stiffens, like mummies and fungi forming green sporulation.Â Keywordsâ€”: black grass jelly plants; Leucopholis rorida F;Metharhizium anisopliae; mortality;effectiveness